Potential predictive role of gut microbiota to immunotherapy in HCC patients: a brief review - Muscolino, Paola; Granata, Barbara; Omero, Fausto; De Pasquale, Claudia; Campana, Stefania; Calabrò, Alessia; D’Anna, Federica; Drommi, Fabiana; Pezzino, Gaetana; Cavaliere, Riccardo; Ferlazzo, Guido; Silvestris, Nicola; et al. (Frontiers in Oncology, 2023)
The recent evolution of immunotherapy has revolutionised the treatment of hepatocellular carcinoma (HCC) and has led to new therapeutic standards. The advances in immunotherapy have been accompanied by the recognition of the role of the gut-liver axis in the progression of HCC but also of the clinical relevance of the gut microbiota, which influences host homeostasis but also cancer development and the response to treatment. Dysbiosis, by altering the tumour microenvironment, favours the activation of intracellular signalling pathways and promotes carcinogenesis. The gut microbiota, through their composition and immunomodulatory role, are thus strong predictors of the response to immune checkpoint inhibitor (ICI) treatment as well as an available target to improve ICI efficacy and reduce drug toxicities. In this review we examine the novel role of the gut microbiota as biomarkers in both the diagnosis of HCC and the clinical response to immunotherapy as well as its potential impact on clinical practice in the future.